2021
DOI: 10.1097/md.0000000000027255
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of red blood cell distribution width in predicting 3-month functional outcome of patients undergoing thrombolysis treatment for acute ischemic stroke

Abstract: This study was performed to determine whether red blood cell distribution width (RDW) is associated with 3-month poor functional outcome in patients undergoing thrombolytic therapy for acute ischemic stroke. RDW was measured in patients with thrombolytic therapy in emergency department. Functional outcome was assessed after 3 months and poor functional outcome was defined as modified Rankin scale 3 to 6. A total of 240 patients were enrolled, and 82 (34.2%) had a poor functional outcome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…30 However, high hematocrit increases protein infiltration into the vessel wall, triggers platelet adhesion to the sub endothelium, and increases the risk of blood flow stagnation, which increases the risk of atherosclerosis. 31 Previous studies showed similar results to this study, that hematocrit was not associated with the short-term outcomes of ischemic stroke patients, 32 and was not associated with ischemic stroke mortality in the first 30 days. 29 The mean age of the patients in this study, as stated by Ozaita, et al (1987) 33 and Bhatia, et al (2004) 34 , were in the same range (59.46 + 11.64, 60.9 + 12.8, and 59.4 + 11.2 years old, respectively), which is younger than 67.9 years old, the average age in a study conducted by Sico, et al (2018).…”
Section: Discussionsupporting
confidence: 87%
“…30 However, high hematocrit increases protein infiltration into the vessel wall, triggers platelet adhesion to the sub endothelium, and increases the risk of blood flow stagnation, which increases the risk of atherosclerosis. 31 Previous studies showed similar results to this study, that hematocrit was not associated with the short-term outcomes of ischemic stroke patients, 32 and was not associated with ischemic stroke mortality in the first 30 days. 29 The mean age of the patients in this study, as stated by Ozaita, et al (1987) 33 and Bhatia, et al (2004) 34 , were in the same range (59.46 + 11.64, 60.9 + 12.8, and 59.4 + 11.2 years old, respectively), which is younger than 67.9 years old, the average age in a study conducted by Sico, et al (2018).…”
Section: Discussionsupporting
confidence: 87%
“…RDW is an indicator of the variation in circulating erythrocyte volume and is routinely measured during complete blood count analysis, which is commonly used in the differential diagnosis of various types of anemias and iron or vitamin de ciency (Salvagno et al 2015). A growing body of studies has identi ed an association between high RDW levels and poor prognosis in AIS patients (Ani and Ovbiagele 2009; Kim et al 2021). RDW levels of ischemic stroke patients was much higher than that of those with no strokes (Jia et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…15 Yogitha and Kumar (2019), Turcato et al (2017), and Kim et al (2021) also had the same results. [16][17][18] Meanwhile, the MCV value of dependent groups was lower than independent groups that indicated low RDW value increased the risk of 30-day disability without any statistically significant p-value (p>0.05) because of too many variations in subjects (standard of deviations >2) and the subjects were only mild and moderate stroke, so the distribution of data was uneven. Low MCV with poor clinical outcome in ischemic stroke was also found in Hatamian et al (2014) 's study, but it contradicted the cohort study conducted by Wu et al (2018).…”
Section: Discussionmentioning
confidence: 99%